Efecto de lactosuero dulce y alga espirulina sobre las características fisicoquímicas, organolépticas y porcentaje proteico de una bebida refrescante de mango. - Ferrín Ferrín, Pablo Antonio (2022)
The aim of this research was to evaluate the effect of sweet whey and spirulina algae on the physicochemical and organoleptic characteristics and protein percentage of a refreshing mango drink, applying the experimental method where two factors were studied: the percentage of sweet whey and the percentage of spirulina algae; evaluating their effect on the dependent variables which were the physicochemical characteristics: pH, titratable acidity and °Brix; organoleptic characteristics: odor, color, flavor and texture and the protein percentage; in addition, the stability of the drink during storage was evaluated by means of microbiological counts. A Completely Randomized Design (CRD) was applied in a bifactorial AxB arrangement, assigning three replicates to each treatment, obtaining 18 experimental units. As results, it was obtained that all treatments complied with the physicochemical parameters of NTE INEN 2304:2017; according to statistical tests, "a1" and "b3" were chosen as the best in pH and acidity, respectively; likewise, after evaluating the treatments, "T3" was chosen as the best combination that favorably influenced the physicochemical characteristics. The protein analysis of the treatments showed that all the combinations favorably increased the protein percentage, observing that "T4" was the treatment that presented the highest protein value with 0.99%. As for the microbiological count, the beverage remained stable during storage, complying with the requirements of NTE INEN 2304:2008. On the other hand, in the sensory evaluation carried out on 70 untrained tasters, the most pleasant treatments were "T3" and "T6".